Association of psychological distress, smoking and genetic risk with the incidence of lung cancer: a large prospective population-based cohort study - Zhang, Jing; Wang, Yi; Hua, Tingting; Wei, Xiaoxia; Jiang, Xiangxiang; Ji, Mengmeng; Ma, Zhimin; Huang, Yanqian; Wang, Hui; Du, Lingbin; Zhu, Meng; Xu, Lin; et al. (Frontiers in Oncology, 2023)
Background: Emerging evidence suggests a potential link between psychological distress (anxiety and depression) and lung cancer risk, however, it is unclear whether other factors such as tobacco smoking and genetic susceptibility modify the association.We included 405,892 UK Biobank participants free of cancer at baseline. Psychological distress was measured using the Patient Health Questionnaire-4 (PHQ-4). A polygenic risk score (PRS) was calculated using 18 lung cancer-associated genetic loci.Multivariable Cox regression models were used to estimate hazard ratios (HRs) and 95% confidence intervals (CIs).Results: During a median follow-up of 7.13 years, 1754 lung cancer cases were documented.The higher score of psychological distress was associated with an increased risk of lung cancer (HRper 1-SD= 1.07, 95% CI: 1.02-1.11) after adjustment for smoking and other confounders.Mediation analysis revealed that 16.8% (95% CI: 13.0%-20.6%) of the distress-lung cancer association was mediated by smoking. Compared with never smokers with no distress, participants with heavy smoking and high distress had the highest risk of lung cancer (HR=18.57, 95% CI: 14.51-23.76). Both multiplicative and additive interactions were observed between smoking and psychological distress in lung cancer. Furthermore, the greatest relative increase in risk was observed among those with high genetic risk and high distress (HR=1.87, 95%CI: 1.50-2.33), and there was a significant additive interaction between the PRS and psychological distress.Our results indicate that psychological distress was associated with an elevated 4 risk of incident lung cancer, and such relation was modified by tobacco smoking and genetic susceptibility.